2012
DOI: 10.1021/la302260a
|View full text |Cite
|
Sign up to set email alerts
|

Water Absorption of Poly(methyl methacrylate) Measured by Vertical Interference Microscopy

Abstract: PMMA (poly(methyl methacrylate)) is widely used to prepare orthopedic cements. They are in direct contact with cells and body fluids. PMMA, despite its hydrophobic nature, can absorb ~2% w/w water. We have evaluated by vertical interference microscopy if water absorption can produce a significant swelling in different types of PMMA blocks: pure, with a plasticizer, with a cross-linker, and in two types of commercial bone cements. Graphite rods which do not swell in water were used as internal standard. Hardnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 25 publications
(30 reference statements)
3
52
0
Order By: Relevance
“…It is well known that hydrophobic polyMMA can contain approximately 2 wt% of water. [34] Our result was consistent with this value, and the water could only be classified as non-freezing water. Based on this value, 2 wt%, the number of non-freezing water molecules governed by the MMA unit is estimated to be 0.11.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…It is well known that hydrophobic polyMMA can contain approximately 2 wt% of water. [34] Our result was consistent with this value, and the water could only be classified as non-freezing water. Based on this value, 2 wt%, the number of non-freezing water molecules governed by the MMA unit is estimated to be 0.11.…”
supporting
confidence: 89%
“…Thus, the temperature of the sample increased during each XRD scan. [34] The intensities of the crystalline peaks at 2θ = 22.9°, 24.4°, and 26.1°in the diffraction patterns for each scan were summed, and the changes in the intensities (crystallinity) as a function of the temperature were investigated.…”
Section: Definition Of the Water Structure And Determination Of It Usmentioning
confidence: 99%
“…4c, d). The top surface of composite film changed from smooth (Stage I) to coarse porous (Stage II), due to water diffusion, swelling of PMMA into pores [42]. Meanwhile, the crystal structures of the two stages were detected by XRD.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with the study of Assuncao et al [37], who reported that storage in saliva could significantly reduce the hardness of the PMMA resin after 15, 30, and 60 days’ treatment. Moreover, it is reported that after 24 h immersion in the water, the PMMA matrix can significantly swell in the lateral and vertical directions [38], indicating that the solvent molecules penetrate into the PMMA matrix and break the intermolecular bonding between polymer networks. Once the matrix network is broken, the properties of PMMA will get worse inevitably.…”
Section: Discussionmentioning
confidence: 99%